MODERN METHODS OF LABORATORY DIAGNOSTICS OF PYELONEPHRITIS - Kudratova Z. E.; Utayeva N. B.; Zulfiqarova M. Ya.; Do’stmurodova X. M.; Jonqobilova H. U. (Web of Journals Publishing, 2024)
Pyelonephritis is an infectious and inflammatory disease of the kidneys with predominant involvement of the calyx and tubulointerstitial tissue, often involving the tubular apparatus. The main causative agents are Gram-positive bacilli of the Enterobacter family, of which Escherichia coli accounts for 80%, less frequently occurring Proteus, Klebsiella, etc. [2,4,6,9].
Keywords: dysuria, inflammation, tubulointerstitial tissue, pyelonephritis, calyx-lochanous system.